Baurusuquídeos da Bacia Bauru (Cretáceo Superior, Brasil) - Felipe Mesquita de Vasconcellos; João Tadeu Arruda; Ismar de Souza Carvalho (Anuário do Instituto de Geociências, 2004)
The baurusuchids are medium-sized crocodylomorphs withterrestrial habits, found in the Gondwana Cretaceous basins of SouthAmerica and Paleogene basins of Europe and Africa. Since 1945 manyskeletal remains have been found on Western of São Paulo State, rocks of Adamantina Formation, Bauru Basin (Late Cretaceous). Thevicinities of General Salgado County, São Paulo State, had revealedwell-preserved and articulated fossils of baurusuchids, allowing studieson the their paleoecology and paleobiology.